THE USING OF RIDDLE TECHNIQUE TO INCREASE STUDENTS’ VOCABULARY MASTERY IN DESCRIBING PEOPLE AT SMA SWASTA KARTIKA 1-4 PEMATANGSIANTAR - Tiodora Silalahi; Dina Syahfitri Tanjung (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2019)
The objective of the research is to analyze the effect of the using Riddle Technique to increase the students’ vocabulary mastery. This research is conducted in SMA Swasta Kartika 1-4 Pematangsiantar. The population of this research is class X at SMA Swasta Kartika Pematangsiantar. In which total class X are 6 classes as many as totally is 228 students. In this research, the researcher uses random sampling. the sample of this research is students of X IS-1at SMA Swasta Kartika 1-4 Pematangsiantar, as many as 38 students and this research was just conducted one class with two cycle. This research method use a quantitative method and was designed in a Classroom Action Research. The focus of this research is intended to answer the problem about teaching vocabulary by using riddle technique to the tenth IS-1 grade students of SMA Swasta Kartika Pematangsiantar is effective or not. In this part, the data is calculated to show the total of score of pre-test and post-test, to show the avarage score of pre-test and post-test, to show the standart deviation and to show the significant difference.From the data analysis above the total score of pre-test is 1911 and the total score of post-test I is 3169. The avarage of post-test I is 83,39. Then the researcher do the post-test II and the total score is 3437. The avarage of the post-test II is 90,45. The value of mean score different is 7,06. The value of t-test is 9,29, the standart deviation is 8 and the significant difference is 0,9.Based on the result of the data analysis, it was obtained that there is difference of post-test I and post-test II namely : the mean score different is 7,06, t-test is 9,29, the standart deviation is 8 and the significant difference is 0,9. It means that the use of riddles technique is effective for teaching vocabulary to the tenth grade IS-1 SMA Swasta Kartika Pematangsiantar. From the result of the research can be conclude that riddle technique can give effect to increase students’ vocabulary mastery in describing people